2020
DOI: 10.1093/mnrasl/slaa055
|View full text |Cite
|
Sign up to set email alerts
|

Crucial role of neutron diffusion in the crust of accreting neutron stars

Abstract: Observed temperatures of transiently accreting neutron stars in the quiescent state are generally believed to be supported by deep crustal heating, associated with nonequilibrium exothermic reactions in the crust. Traditionally, these reactions are studied by considering nuclear evolution governed by compression of the accreted matter. Here we show that this approach has a basic weakness, that is that in some regions of the inner crust the conservative forces, applied for matter components (nuclei and neutrons… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In this work we have used the models by Haensel & Zdunik (2008) and Fantina et al (2018) for the deep crustal heating. Recently, Chugunov & Shchechilin (2020) and Gusakov & Chugunov (2020) have shown that diffusion of neutrons in the inner crust, neglected in the previous studies, can be essential for composition, equation of state, and heating of the accreted inner crust. An impact of these effects on thermal evolution of transiently accreting neutron stars remains to be studied in a future work.…”
Section: Discussionmentioning
confidence: 99%
“…In this work we have used the models by Haensel & Zdunik (2008) and Fantina et al (2018) for the deep crustal heating. Recently, Chugunov & Shchechilin (2020) and Gusakov & Chugunov (2020) have shown that diffusion of neutrons in the inner crust, neglected in the previous studies, can be essential for composition, equation of state, and heating of the accreted inner crust. An impact of these effects on thermal evolution of transiently accreting neutron stars remains to be studied in a future work.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, we adopt Ref. [11] as the traditional deep crustal heating input, an improved deep crustal heating model by considering the diffusion of neutrons in the inner crust is proposed [13][14][15]. It's also interesting to investigate the quiescent luminosity of SXTs with this modern deep crustal heating.…”
Section: Discussionmentioning
confidence: 99%
“…Observed quiescent luminosities of transiently accreting neutron stars are generally believed to be held by deep crustal heating with the release of ∼ 1 − 2 MeV per accreted nucleon [8][9][10][11][12], which is produced by the non-equilibrium nuclear reactions such as electron captures, neutron emission/absorption and pycnonuclear reaction due to the continuous compression during outburst phase. It's worth to mention that Chugunov and collaborators have pointed out that the mobility of neutrons in the inner crust could strongly suppress the heat release and drastically change its distribution over density [13][14][15], compared with the conventional deep crustal heating models (Hasensel et al Refs. [8][9][10][11][12]).…”
Section: Introductionmentioning
confidence: 99%
“…Namely, all of them implicitly neglect the redistribution of unbound neutrons in the inner crust. It has recently been shown that this approximation is incorrect (Chugunov & Shchechilin 2020) and leads to violation of the neutron hydrostatic/diffusion (nHD) equilibrium in the inner crust (Gusakov & Chugunov 2020, hereafter GC20). In fact, the nHD equilibrium condition, given by µ ∞ n ≡ µne ν/2 = const (here µn is the local neutron chemical potential, including the rest mass and e ν/2 is the redshift factor), should be considered simultaneously with the hydrostatic TOV equations.…”
Section: Introductionmentioning
confidence: 99%